The Influence of Self-control and Religiosity on the Academic Flow of Islamic Education Students at Universitas Muhammadiyah Yogyakarta, Indonesia - Aqmar, Sovia Nabila (Universitas Muhammadiyah Yogyakarta, 2025)
This study aimed to analyze the level of self-control, religiosity, and academic flow in students as well as the influence of self-control and religiosity on academic flow in students. This study used a descriptive, quantitative approach. The study population comprised 108 students from a private university in Yogyakarta, followed by a sample study of 85 students. Simple random sampling was used. The instruments were a Likert-scale questionnaire and interviews. A double linear regression test was used for the data analysis. The results of the study showed that 1) the self-control rate of students in the average category was 68.2%, 2) the religiosity of the students in the medium category was 78.0%, 3) the academic flow rate for the average student was 77.6%, and 4) the F test or simultaneous self-controlled and religious influence together on academic flows with a significance of 0.05. The r-square value of the influence of self-control and religiosity academic flows was 30.5%, while the other 69,5% were influenced by other variables not mentioned in the independent variable of this study. The combination of self-control and religiosity toward academic flow provides a new perspective that integrates psychological and spiritual dimensions. In the world of education, increased self-control and religiosity give students good self-control, value the learning process, and regard it as worship and moral responsibility, which can support more orderly academic development and student growth in higher academic achievement.